2019
DOI: 10.1007/jhep08(2019)115
|View full text |Cite
|
Sign up to set email alerts
|

Non-Abelian T-duality as a transformation in Double Field Theory

Abstract: Non-Abelian T-duality (NATD) is a solution generating transformation for supergravity backgrounds with non-Abelian isometries. We show that NATD can be described as a coordinate dependent O(d,d) transformation, where the dependence on the coordinates is determined by the structure constants of the Lie algebra associated with the isometry group. Besides making calculations significantly easier, this approach gives a natural embedding of NATD in Double Field Theory (DFT), a framework which provides an O(d,d) co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(78 citation statements)
references
References 77 publications
3
75
0
Order By: Relevance
“…A new formulation of DFT on group manifolds (called DFT WZW ) has been developed in [20][21][22], and in the recent works [23,24], the PL T -duality has been studied in the framework of DFT WZW . In more recent papers [7,25], the non-Abelian T -duality and the PL T -duality have been discussed by using another approach, called the gauged DFT [26][27][28][29][30][31] (see also [32,33] for recent discussion on the Drinfel'd double and related aspects in DFT). Thus, DFT is now not restricted to Abelian T -duality but can be applied also to the non-Abelian extensions.…”
Section: Introductionmentioning
confidence: 99%
“…A new formulation of DFT on group manifolds (called DFT WZW ) has been developed in [20][21][22], and in the recent works [23,24], the PL T -duality has been studied in the framework of DFT WZW . In more recent papers [7,25], the non-Abelian T -duality and the PL T -duality have been discussed by using another approach, called the gauged DFT [26][27][28][29][30][31] (see also [32,33] for recent discussion on the Drinfel'd double and related aspects in DFT). Thus, DFT is now not restricted to Abelian T -duality but can be applied also to the non-Abelian extensions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently in [25], we showed that the NATD transformation rules obtained in [24] for a generic GS string with isometry group G can be described through the action of a coordinate dependent 1 See also [23], where they arrive at the same result by utilizing the O(d, d) structure of NATD.…”
Section: Introductionmentioning
confidence: 89%
“…Recently, Borsato and Wulff extended their work to homogeneous YB deformations of more general sigma models than PCMs. In their paper [24], they derived the rules for NATD for a generic Green-Schwarz (GS) string with isometry group G, where NATD is applied with respect to a subgroup of G. Then, by using the connection between NATD and homogeneous YB models that they had established in [21], [22], they proposed the form of homogeneous YB deformation for a generic GS sigma model and showed that this gave a natural generalization of the YB deformation of PCMs and supercosets.Recently in [25], we showed that the NATD transformation rules obtained in [24] for a generic GS string with isometry group G can be described through the action of a coordinate dependent 1 See also [23], where they arrive at the same result by utilizing the O(d, d) structure of NATD.…”
mentioning
confidence: 89%
See 2 more Smart Citations